A Case Of Plasmodium Vivax Malaria Treated With Dihydroartemisinin-Piperaquine And Primaquine In A 15-Year-Old Child Returning To Ambon City From A Visit To Timika City - -, Aerlangga (Jurnal Biomedika dan Kesehatan, 2026)
Plasmodium vivax remains an important cause of malaria, especially in children who are at higher risk of complications such as anemia and thrombocytopenia. We report a 15-year-old girl with intermittent fever, cough, and weakness. Laboratory tests showed severe thrombocytopenia and leukocyte abnormalities, and peripheral blood smear confirmed Plasmodium vivax infection. The patient was treated with dihydroartemisinin–piperaquine and primaquine, leading to gradual clinical improvement and clearance of parasitemia. This case highlights that P. vivax malaria in children can mimic other febrile illnesses and cause significant hematologic changes. Early diagnosis and appropriate therapy are essential to prevent complications and relapse. The successful use of dihydroartemisinin–piperaquine with primaquine in this patient demonstrates the importance of radical cure and careful clinical monitoring in pediatric malaria management. Keywords: malaria; plasmodium vivax; children; dihydroartemisinin piperaquine; primaquine